Transfer payment structure and local government fiscal efficiency: Evidence from China - Yongqiu Wu; Yi Huang; Jing Zhao; Yanping Pu (China Finance and Economic Review, 2017)
Background: After revenue-sharing system reform, the proportion of tax refund in fiscal transfer payments continued to decline, and the proportion of categorical grant and condition grant is increased. The paper studies how transfer payment structure effect fiscal efficiency from the perspective of local financial revenue structure. Methods: This paper use the SE-DEA model to measures the financial efficiency, and studies how transfer payment structure effect fiscal efficiency by the quantile regression method. Results: The theoretical and empirical studies indicate that the tax refund is the most effective policy and the categorical grant is more efficient than condition grant. Conclusions: The China's central government should decrease the condition grant and increases the tax refund or categorical grant in transfer payment.
Keywords: 330; Transfer payment; Fiscal efficiency; Quantile regression